Draft Annual Plan 1988-89 Tamil Nadu - Planning Commission (Planning Commission, 1988)
Annual Plan for the year 1988-89 has been drafted to fulfil the larges set the Seventh Five-Year Plan. After undertaking a mid-term appraisal on the progress so far made and the grounds to be covered the programmes for the remaining years have been regulated to achieve the objectives of productivity, employment and food set for the five-year plan. In certain important sectors like rural health, particular attention has been paid to ensure achievement of physical targets in addition to the financial requirements.
State Planning Commission Tamil Nadu